2020
DOI: 10.1021/acs.analchem.0c03765
|View full text |Cite
|
Sign up to set email alerts
|

Direct Analysis of Ion-Induced Peptide Fragmentation in Secondary-Ion Mass Spectrometry

Abstract: Primary-ion-induced fragmentation in organic molecules can strongly influence the results in secondary-ion mass spectrometry (SIMS) of organic and biomolecular samples. In order to characterize this ion-induced fragmentation, oligopeptide samples irradiated in SIMS experiments were investigated by means of desorption/ ionization induced by neutral SO 2 clusters (DINeC). The latter is a nondestructive desorption method for mass spectrometry of biomolecules, which gives direct access to the fragments induced in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 47 publications
0
11
1
Order By: Relevance
“…With the employment of large noble gas cluster primary ions for much softer sputtering, depth-profiling of polymers has been achieved without signal loss during the measurement . Due to the high sputter yield of cluster ions in combination with the localization of primary-ion induced damage at the surface, the material altered by one cluster impact is removed by the next cluster impact at a given site, thus significant damage accumulation and cross-linking does not occur . However, primary ion induced fragmentation is still observed, different from desorption/ionization induced by neutral, low-energy SO 2 clusters as employed in our study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the employment of large noble gas cluster primary ions for much softer sputtering, depth-profiling of polymers has been achieved without signal loss during the measurement . Due to the high sputter yield of cluster ions in combination with the localization of primary-ion induced damage at the surface, the material altered by one cluster impact is removed by the next cluster impact at a given site, thus significant damage accumulation and cross-linking does not occur . However, primary ion induced fragmentation is still observed, different from desorption/ionization induced by neutral, low-energy SO 2 clusters as employed in our study.…”
Section: Resultsmentioning
confidence: 99%
“…As the detailed molecular properties of the polymer molecules determine the electrical and optical properties of these devices, sample characterization is a crucial step for both research and production purposes, thus making a powerful analytical tool mandatory. Secondary-ion mass spectrometry (SIMS) is a widespread method for the characterization of solid samples of polymers and organic materials in general; however, it typically comes with significant fragmentation induced by the primary ions. While this can be an advantage, e.g., for identification of larger molecules or for depth profiling of polymer samples, characterization of sample properties like the mass distribution of the smaller molecules will benefit from a nondestructive approach.…”
Section: Introductionmentioning
confidence: 99%
“…The impurity levels were measured in advance with a magnetic‐sector‐type dynamic‐SIMS using the raster change method 11,12 . The concentrations of carbon, oxygen, hydrogen, and nitrogen were 2 × 10, 15 3 × 10, 15 less than 6 × 10, 15 and less than 2 × 10 14 atoms/cm 3 , respectively. Depth profiling done using dynamic‐SIMS confirmed that the depth‐wise distribution of these elements was uniform and that aggregation had not occurred.…”
Section: Methodsmentioning
confidence: 99%
“…Related to dynamic‐SIMS, time‐of‐flight (TOF)‐SIMS has been employed as a unique analytical technique for chemical as well as elemental characterization at the sample surface. Furthermore, combining sputtering ion beams, such as Ar + , O 2 + , and Cs + , and gas cluster ion beams (GCIB) has enabled depth profiling, and these methods have been used for both inorganic and organic materials 13–16 . TOF‐SIMS has the advantage of qualitative analysis with a higher lateral resolution than dynamic‐SIMS.…”
Section: Introductionmentioning
confidence: 99%
“…(ii) How are the internal energy and the conformation of the molecules influenced by the desorption conditions (cluster size, energy, incidence angle, etc. 12 )? (iii) Would much larger clusters or clusters with a different chemistry be more appropriate to transfer "cool" molecules (thereby preserving their initial conformation)?…”
Section: Introductionmentioning
confidence: 99%